Dystocia Due to Monocephalic Thoracopagus Tetrabrachius Tetrapus Monster in a Murrah Buffalo - Kamboj, Prateek; Yadav, Vinay; Singh, Reetinder; Singh, Satnam (The Indian Journal of Animal Reproduction, 2025)
This case report describes the management of dystocia with two female fetuses joined at the thoracic region (Thoracopagus) and having well developed eight limbs i.e. four forelimbs (Tetrabrachius) and four hind limbs (Tetrapus) and both pelvis are separate (Dicaudatus) with ruptured amniotic sacs and the fetus lodged in the birth canal.